Some Aspects of Correlation of Physical Capital and Infrastructures on Household Food Security: Evidence from Rural Tanzania - Mbukwa, Justine N. (Journal of Economics and Sustainable Development, 2024)
Article published in the Journal of Economics and Sustainable Development Volume 5, Issue 9, Pages 26-34